(untitled) (Global Journal of Science Frontier Research, 2017)
Schistosome are a treamatode, snail-born parasitic of circulatory system in domestic animals and man. Ruminants are usually infected with cercariae by active penetration of the unbroken skin. Schistosoma bovis is the main cause of cattle schistosomiasis and is common in marshy area. A cross sectional study was conducted from November 2015 to March 2016 in and around Bakko town of Oromia, Ethiopia to investigate the prevalence and associated risk factors of bovine schistosomiasis. Simple random sampling technique was used to select 384 study animals and householders, whereas peasant associations (PA) were selected purposively focusing on those residing around Gibe River. Coprological examination with faecal sedimentation technique was used to recover the eggs of schistosoma. This revealed an overall prevalence of 22.92% (88/384) (95%CI: 18.71, 27.12). Multivariate logistic regression was used to examine the strength of association between predictor variables and the occurrence of schistosoma infection.